2005
DOI: 10.1038/sj.bjc.6602895
|View full text |Cite
|
Sign up to set email alerts
|

Role of mammography screening as a predictor of survival in postmenopausal breast cancer patients

Abstract: We examined the effect of population-based screening programme on tumour characteristics by comparing carcinomas diagnosed during the prescreening (N ¼ 341) and screening (N ¼ 552) periods. We identified screen detected (N ¼ 224), interval (N ¼ 99) and clinical cancer (N ¼ 229) cases. Median tumour size and proportion of axillary lymph node negative cases were 1.5 cm and 65% in the screen detected group, 2.0 cm and 44% in cases found outside the screening, and 3.2 cm and 41% in the cases from the prescreening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Although our early analysis does not provide patient follow-up data, the computed 10-year risks of relapse and death probably afford a realistic insight concerning the outcome depending on the mode of detection in our patients. These data accord well with the important findings of a good number of studies [7][8][9][10][11][12][13][14], and notably the superior outcome of screen-detected breast cancers as compared with their symptomatic counterparts. Moreover, the analyses by Joensuu et al [11] and Gill et al [13] suggest that screening-detection itself is an independent favorable prognostic factor that should be taken into consideration when the adjuvant therapy is to be specified.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although our early analysis does not provide patient follow-up data, the computed 10-year risks of relapse and death probably afford a realistic insight concerning the outcome depending on the mode of detection in our patients. These data accord well with the important findings of a good number of studies [7][8][9][10][11][12][13][14], and notably the superior outcome of screen-detected breast cancers as compared with their symptomatic counterparts. Moreover, the analyses by Joensuu et al [11] and Gill et al [13] suggest that screening-detection itself is an independent favorable prognostic factor that should be taken into consideration when the adjuvant therapy is to be specified.…”
Section: Discussionsupporting
confidence: 89%
“…An appreciable number of studies have clearly indicated that the introduction of mammographic screening has been followed by a shift to tumors with better prognostic factors. [7][8][9][10][11][12][13][14] Thus, screen-detected breast cancers are smaller, more frequently lymph node-negative, [7][8][9][10][11][12][13][14] of lower grade, [9,11,13] and consequently need less oncological treatment than their symptomatic counterparts. [11,13] In addition to this stage shift stemming from the earlier detection, the better outcome is explained by the different biological behavior of these early cancers, since the detection by mammographic screening has been shown to be an independent favorable prognostic factor as regards distant metastasis-free survival and overall survival relative to that in symptomatic tumors.…”
Section: Introductionmentioning
confidence: 98%
“…Patients who had their diagnosis mammography performed within the screening framework had better survival of 13.3% at 5 years, and 18.6% at 7 years (Po0.001), whereas the others who had mammography after the onset of clinical symptoms, or because they belonged to a high risk group, had an increased death risk hazard of 2.2 (95% CI ¼ [1.5 -3.2]; Po0.001). Other studies have also found that screening detected smaller tumours with a more favourable prognosis compared with those clinically detected (Fracheboud et al, 2004;Anttinen et al, 2006). However, to our knowledge, mammography itself as a mode of detection has rarely been demonstrated as an independent prognostic factor in women who all had a diagnosis mammography, and in a population-based study, that is to say without any intervention or evaluation.…”
Section: Discussionmentioning
confidence: 79%
“…Th e proportion of in situ and <15 mm invasive carcinomas amongst all screen-detected breast cancers varies in the range of 30-60% [3,16,28], and depends on the time interval since the introduction and the quality and other features of the mammographic screening. Th e fi ndings of numerous comparative analyses are concordant in that screen-detected cancers are smaller, more frequently lymph node-negative and of low grade [17,[28][29][30][31][32][33][34][35]. Some have reported more frequent hormone receptor positivity [4,28,30,[33][34][35]37], HER2 negativity (30,34) and lower proliferation activity by means of Ki67 expression [28,30,32, 34] among screen-detected tumours.…”
mentioning
confidence: 91%